Application of Songs and Movement in Improving Kinesthetic Intelligence in Early Childhood at RA Al Mahabbah - Kharida Shaleha; Afdhalina; Novi Cynthia Yusnita; Rahmadini Aisyah (Outline Journal of Community Development, 2024)
Early Childhood Education (PAUD) as a human resource development strategy isa very fundamental and strategic central point for future development. Therefore, the application of songs and movements is based on the underdevelopment of kinesthetic intelligence owned by children at RA Al Mahabbah, the quiz aims to determine the increase in intelligence children's kinesthetics after learning is applied. Learning movements and songs is one of the ways teachers present learning material in themes. This makes it easier for students to remember the themes in learning. This application aims to describe song and movement learning to improve the kinesthetic intelligence of early childhood. In this case, the Raudhatul Athfal Al Mahabbah Educational Institution realizes the importance of stimulating and even educating its children at an early age. Considering the importance of this, the Application of Songs and Movement in Improving Kinesthetic Intelligence in Early Childhood was held at the RA Al Mahabbah at Jl. Batang Kuis Lubuk Pakam Desa Baru Dusun II No.109 Batang Kuis , Deli Serdang, Sumatera Utara.